Antileukemic Effect of Tualang Honey on Acute and Chronic Leukemia Cell Lines - Nik Man, Nik Muhd Khuzaimi; Hassan, Rosline; Cheng, Yong Ang; Abdullah, Abu Dzarr Ganesh; Mohd Radzi, Muhammad Amiro Rasheeq; Sulaiman, Siti Amrah (Hindawi Publishing Corporation, 2015)
Complementarymedicine using natural product as antitumor is on the rise.Much research has been performed on Tualang Honey and it was shown to have therapeutic potential in wound healing, and antimicrobial activity and be antiproliferative against several cancer models such as human osteosarcoma (HOS), human breast (MCF-7 and MDA-MB-231), and cervical (HeLa) cancer cell lines. To date, there was limited study on antileukemic properties of Tualang (Koompassia excelsa) Honey. The aim of this study was to evaluate the antileukemic effect of Tualang Honey on acute and chronic leukemia cell lines. Leukemia cell lines (K562 and MV4-11) and human mononuclear cell isolated from peripheral blood were grown in RPM1 1640 culture medium. The cells were incubated with increasing concentrations of Tualang Honey. After incubation, the evaluation of viability and apoptosis was performed. The morphological changes of leukemia cells were the presence of cytoplasmic blebs followed by apoptotic bodies and round shape of cells. IC50 against K562 and MV4-11 was determined. Tualang Honey gave 53.9% and 50.6% apoptosis activity on K562 and MV4-11, respectively, while on human mononuclear cell it was 37.4%. Tualang Honey has the apoptosis-inducing ability for acute and chronic myeloid leukemia (K562 and MV4-11) cell lines.